UNSUR-UNSUR BUDAYA SUKU BAJO DALAM NOVEL MATA DAN MANUSIA LAUT KARYA OKKY MADASARI: KAJIAN ANTROPOLOGI SASTRA - Syahroma Eka Suryani; Endang Rahmawati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2022)
This study aims to analyze the anthropological aspects of literature as seen on the side of the cultural elements of the Bajo tribe in the novel Mata dan Manusia Laut by Okky Madasari. This research is included in the type of literature research, while the research method used is descriptive qualitative analysis. The data is in the form of documents entitled Mata dan Manusia Laut. The theory used in this research is the theory of literary anthropology which is based on cultural elements. There are seven of the findings data based on Bajo cultural elements in the novel Mata and Manusia Laut, namely (1) Human Life Tools is 29 data, (2) 9 data about livelihood, (3) Social system with 14 data, (4) Language system is 3 data (5) 6 data of various types of art, (6) Knowledge system with 16 data and (7) Religion system with 24 data.